Preparation method and application of titanium surface antibacterial coating
By preparing FeS2 coating on the surface of titanium material, the problem of insufficient antibacterial performance of titanium material is solved, and its antibacterial performance and biocompatibility are significantly improved. It is suitable for medical materials.
Patent Information
- Application Number
- CN202510200270.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-24
AI Technical Summary
Titanium materials have shortcomings in antibacterial properties, which may increase the risk of postoperative bacterial colonization and infection.
The FeS2 coating was prepared on the pure titanium surface by vertical solvothermal method, and the sodium titanate layer was formed by pickling and alkalizing treatment, thereby increasing the binding force between the FeS2 coating and the titanium substrate.
It significantly improves the antibacterial properties of pure titanium materials and improves the biocompatibility of pure titanium materials for medical use. It is simple to operate and low energy consumption, and is suitable for large-scale production.
Smart Images

Figure CN119685823A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface treatment, and particularly relates to a preparation method and application of an antibacterial coating on a titanium surface. Background Art
[0002] In the current field of tissue structure restoration and treatment, biomedical metal materials have a series of excellent characteristics such as high reliability, fatigue wear resistance, and excellent processing and forming performance, and have been widely used in modern clinical medicine. At present, biomedical metal materials used in medical clinical applications mainly include 316L stainless steel, titanium and its alloys, and cobalt-based alloys.
[0003] In the field of orthopedic implants, titanium is widely used due to its high strength, corrosion resistance and biocompatibility. However, titanium materials have inherent deficiencies in antibacterial properties, which may increase the risk of postoperative bacterial colonization and infection. Therefore, improving the antibacterial properties of titanium materials has become an important direction of current research. Summary of the invention
[0004] In order to improve the antibacterial properties of pure titanium materials, the present invention provides a method for preparing an antibacterial coating on a titanium surface. The method uses a vertical solvothermal method to prepare a FeS2 coating with a dense structure and good bonding with a pure titanium substrate on the surface of pure titanium. The antibacterial properties of pure titanium materials can be improved, thereby enhancing the biocompatibility of medical pure titanium materials.
[0005] The present invention also provides an application of a method for preparing an antibacterial coating on a titanium surface in preparing biomedical materials or medical devices.
[0006] The present invention is achieved through the following technical solutions: The present invention provides a method for preparing an antibacterial coating on a titanium surface, the preparation method comprising: Pickling the surface of the titanium material to obtain the pickled titanium material; placing the acid-washed titanium material in an alkali solution for alkalization to form a sodium titanate layer, thereby obtaining an alkalized titanium material; The alkalized titanium material is vertically placed in a reaction solution containing an iron source and a sulfur source to perform a hydrothermal reaction to obtain a titanium material containing a FeS2 coating; Wherein, the iron source in the reaction solution includes any one of ferric chloride, ferrous gluconate, ferrous sulfate and ferric nitrate, and the sulfur source includes any one of tetraethylthiuram disulfide, thiourea and thioacetamide.
[0007] Furthermore, pickling the surface of the titanium material to obtain the pickled titanium material specifically includes: A mixed acid solution is used to pickle the surface of the titanium material to obtain a pickled titanium material; The mixed acid solution is prepared by mixing hydrofluoric acid, nitric acid and water in a volume ratio of 1:4:5.
[0008] Furthermore, the acid-washed titanium material is placed in an alkaline solution for alkalization to form a sodium titanate layer to obtain an alkalized titanium material, which specifically includes: The acid-washed titanium material is placed in a 1-10 mol / L sodium hydroxide solution or a potassium hydroxide solution for alkalization for 20-28 hours to form a sodium titanate layer, thereby obtaining an alkalized titanium material.
[0009] Furthermore, the alkalized titanium material is vertically placed in a reaction solution containing an iron source and a sulfur source to perform a hydrothermal reaction to obtain a titanium material containing a FeS2 coating, which specifically includes: The alkalized titanium material is vertically placed in a reaction solution containing an iron source and a sulfur source, and a hydrothermal reaction is carried out at 140 to 200° C. The reaction time is 12 to 24 hours to obtain a titanium material containing a FeS2 coating.
[0010] Furthermore, in the reaction solution, the concentration of the iron source is 0.03-0.06 mol / L, and the concentration of the sulfur source is 0.04-0.08 mol / L; The solvent of the reaction solution includes ethanol.
[0011] Preferably, in the reaction solution, the molar ratio of the iron source to the sulfur source is 1:4.5.
[0012] Preferably, the titanium material includes a pure titanium sheet or a titanium alloy sheet.
[0013] Based on the same inventive concept, the present invention provides a titanium material containing a FeS2 coating, and the titanium material containing a FeS2 coating is prepared by the above-mentioned method for preparing an antibacterial coating on a titanium surface.
[0014] Based on the same inventive concept, the present invention provides a method for preparing an antibacterial coating on a titanium surface and its application in preparing biomedical materials or medical devices.
[0015] Based on the same inventive concept, the present invention also provides an application of a titanium material containing a FeS2 coating in the preparation of biomedical materials or medical devices.
[0016] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages: The present invention discloses a method for preparing an antibacterial coating on a titanium surface. The method comprises the following steps: performing an alkalization treatment on the surface of an acid-washed titanium material to form a sodium titanate layer, and then hydrothermally growing a FeS2 coating on the surface of the alkalized titanium material using a vertical solvent thermal method. The FeS2 coating obtained by hydrothermal preparation by vertically hanging or placing it on a titanium net has a dense structure and can improve the antibacterial properties of the pure titanium material, thereby improving the biocompatibility of the medical pure titanium material. The method is simple to operate, has low energy consumption, and can be prepared in large quantities. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0018] Figure 1 This is a schematic diagram of the titanium sheet being placed horizontally on the inner lining of the reactor in Example 1; Figure 2 This is a schematic diagram of the titanium sheet in Example 2 being suspended on the titanium mesh at an angle of 60° to the horizontal plane; Figure 3 Schematic diagram of the titanium sheet in Example 3 being suspended on the titanium wire at 90° to the horizontal; Figure 4 The SEM image of the FeS2 coating obtained in Example 1; Figure 5 The bacterial morphology of the FeS2 coating after antibacterial coating obtained in Example 1; Figure 6 This is a SEM image of the FeS2 coating obtained on the pure titanium surface in Example 2 of the present invention; Figure 7 The bacterial morphology of the FeS2 coating after antibacterial coating obtained in Example 2; Figure 8 This is a SEM image of the FeS2 coating obtained on the pure titanium surface in Example 3; Fig. 9 The bacterial morphology of the FeS2 coating after antibacterial coating obtained in Example 3; Fig.10 This is the bacterial morphology after antibacterial treatment on the titanium surface in Control Example 1; Fig.11 UV-vis spectra of ox-TMB catalyzed by control group 1, example 1, example 2, example 3, 2 mM FeS2 and 2 mM FeSO4. DETAILED DESCRIPTION
[0019] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0020] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0021] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0022] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0023] The overall idea of the present invention is as follows: Mechanical morphology antibacterial refers to inhibiting bacterial attachment and growth by adjusting the surface morphology and microstructure of the material. The key points include increasing surface roughness to reduce bacterial attachment, using micro-nanostructures to interfere with bacterial growth, designing specific shapes to physically destroy bacterial cell walls, combining antibacterial coatings to enhance the effect, and ensuring good biocompatibility to promote cell attachment and inhibit bacteria. The antibacterial properties of the material can be significantly improved and the risk of infection can be reduced by reasonable design and optimization of the mechanical morphology.
[0024] Iron sulfide Nanoparticles have shown excellent potential in antimicrobial applications, and their peroxidase (POD) activity is generally superior to that of traditional iron oxide nanozymes. The antibacterial mechanism of Active free radicals generated. In addition, iron sulfide nanoparticles, as nanozymes with both peroxidase (POD)-like and catalase (CAT) activities, can efficiently catalyze hydrogen peroxide and promote the release of hydrogen polysulfide, further enhancing its antibacterial efficiency. This property makes it an ideal candidate for the development of new and efficient antibacterial materials, providing a new technical direction and theoretical support.
[0025] The main components of the FeS2 coating prepared by the present invention are iron and sulfur, both of which are nutrients required by the human body. Therefore, it is more easily accepted in terms of biosafety in antibacterial treatment of organisms than other metal sulfides. The FeS2 coating material prepared by the present invention has broad application prospects in the fields of medicine and biotechnology.
[0026] Specifically, the present invention provides a method for preparing an antibacterial coating on a titanium surface, the preparation method comprising: S1. Pickling the surface of the titanium material to obtain a pickled titanium material; S2. placing the pickled titanium material in an alkali solution for alkalization to form a sodium titanate layer to obtain an alkalized titanium material; S3. The alkalized titanium material is vertically placed in a reaction solution containing an iron source and a sulfur source, and a hydrothermal reaction is performed to obtain a titanium material containing a FeS2 coating; Wherein, the iron source in the reaction solution includes any one of ferric chloride, ferrous gluconate, ferrous sulfate and ferric nitrate, and the sulfur source includes any one of tetraethylthiuram disulfide, thiourea and thioacetamide.
[0027] In the present invention, the purpose of pickling the surface of the titanium material is to remove impurities on the titanium surface.
[0028] In the present invention, the purpose of placing the pickled titanium material in an alkaline solution for alkalization is to form a sodium titanate layer, the surface morphology of which can improve the bonding force between the substrate and FeS2. At the same time, a layer of alkaline solution is attached to the surface so that a thin layer is formed on the surface when the titanium material is immersed in a solution mixed with an iron source and a sulfur source. layer, which is beneficial to the subsequent formation of FeS2.
[0029] In the present invention, the alkalized titanium material is placed at a certain angle to the horizontal plane in a reaction solution containing an iron source and a sulfur source for a solvothermal reaction. The advantages of placing the titanium sheet non-horizontally are: 1. Uniform deposition: Non-horizontal placement of titanium sheets can reduce the uneven deposition of materials on the substrate surface due to gravity. This placement is conducive to forming a uniform film or coating on the entire substrate because the influence of gravity is relatively uniform in the vertical direction.
[0030] 2. Reduce particle accumulation: When the titanium sheet is not placed horizontally, the deposited particles are not easy to accumulate on the substrate surface, thereby reducing mutual occlusion between particles and promoting more uniform growth.
[0031] 3. Optimize solution flow: The non-horizontally placed substrate of the titanium sheet is conducive to the natural convection and flow of the solution, ensuring that the reactants flow evenly across the substrate surface. This flow can promote uniform growth of the material and improve the quality of the material.
[0032] 4. Space utilization efficiency: The non-horizontal placement of the titanium sheet can more effectively utilize the space of the reactor, allowing multiple substrates to be processed simultaneously in one reactor, thereby improving production efficiency.
[0033] In the present invention, The coating has an antibacterial effect. The principle is that the nanosheet mesh structure surface has a significantly improved bactericidal efficiency compared to a flat surface, which is mainly attributed to the larger total contact adhesion area. This increased surface area can enhance the tensile strain of the cell membrane, and when it reaches a certain level, it will cause cell lysis, thereby achieving mechanical sterilization. The mechanical sterilization mechanism exerts pressure on bacteria through physical structures, ultimately leading to the rupture of the bacterial cell membrane and cell death. This method does not rely on chemical agents, so it is expected to slow the development of drug resistance and provide long-lasting effects in various antibacterial applications. At the same time, Ferrous ions in Can catalyze hydrogen peroxide under certain conditions Generate hydroxyl radicals This process is called the Fenton reaction. Hydroxyl free radicals are a strong oxidant that can effectively destroy the cell wall, membrane structure and internal biological molecules of bacteria, thereby achieving antibacterial effects.
[0034] In the present invention, tetraethylthiuram disulfide is used as the sulfur source. Compared with other vulcanizing agents, the byproducts generated by the decomposition of tetraethylthiuram disulfide are relatively simple, which reduces the possibility of impurities being introduced, thereby improving the purity of the product.
[0035] After the titanium sheet is alkalized, a layer of sodium titanate is formed on the surface of the titanium sheet. During the hydrothermal process, a network structure is formed to promote the adhesion of ferrous sulfide on the titanium surface. After the titanium sheet is alkalized, the titanium sheet is directly placed in a reactor for reaction. At this time, the residual sodium hydroxide reacts with the iron source in the solution to generate , enriching the iron source on the surface. When placed horizontally, spherical FeS2 will be generated on the surface, which is due to the FeS2 formed in the solution falling on the titanium surface. Later, when the titanium sheet is not placed horizontally, sulfidation will lead to the appearance of a dense layer of ferrous sulfide lamellar structure.
[0036] Wherein, step S1 specifically includes: A mixed acid solution is used to pickle the surface of the titanium material to obtain a pickled titanium material; The mixed acid solution is prepared by mixing hydrofluoric acid, nitric acid and water in a volume ratio of 1:4:5.
[0037] Step S2 specifically includes: The acid-washed titanium material is placed in a 1-10 mol / L sodium hydroxide solution or a potassium hydroxide solution for alkalization for 20-28 hours to form a sodium titanate layer, thereby obtaining an alkalized titanium material.
[0038] Step S3 specifically includes: The alkalized titanium material is vertically placed in a reaction solution containing an iron source and a sulfur source, and a hydrothermal reaction is carried out at 140 to 200° C. The reaction time is 12 to 24 hours to obtain a titanium material containing a FeS2 coating.
[0039] In the present invention, the hydrothermal reaction temperature is 140-200°C, and tetraethylthiuram disulfide releases sulfur by decomposition under solvent thermal conditions. Too high a temperature will damage the lining of the reactor, and too low a temperature will cause tetraethylthiuram disulfide to fail to decompose and release sulfur at a sufficient temperature.
[0040] In the reaction solution, the concentration of the iron source is 0.03-0.06 mol / L, and the concentration of the sulfur source is 0.04-0.08 mol / L; The solvent of the reaction solution includes ethanol.
[0041] Preferably, in the reaction solution, the molar ratio of the iron source to the sulfur source is 1:4.5.
[0042] In the present invention, the molar ratio of the iron source to the sulfur source is 1:4.5, which has the advantage of ensuring that the iron source reacts completely.
[0043] The preparation method and application of the antibacterial coating on titanium surface of the present invention will be described in detail below in combination with examples and experimental data.
[0044] The technical solution of the present invention mainly includes two steps: one is equipment pretreatment; the other is preparation process. Equipment pretreatment mainly includes: Pretreatment of polytetrafluoroethylene-lined reactor and titanium wire and titanium mesh: Before the hydrothermal reaction, put the titanium wire or titanium mesh into the lining of the polytetrafluoroethylene-lined reactor, and then add 30 mL of ultrapure water and 15 mL of 66-68% nitric acid to the lining. Tighten the reactor and then clean it at 140 °C for 8 h.
[0045] Example 1 The present embodiment provides a method for preparing an antibacterial coating on a titanium surface, which specifically includes: (1) Cutting a TA2 pure titanium sheet into a size of 0.3×10×10 mm, and pickling the surface of the TA2 pure titanium sheet with a mixed acid solution to obtain an acid-washed titanium material, wherein the mixed acid solution is prepared by mixing hydrofluoric acid, nitric acid, and water in a volume ratio of 1:4:5; (2) placing the acid-washed TA2 pure titanium sheet in a 5 mol / L sodium hydroxide solution for alkalization for 24 h to form a sodium titanate layer to obtain an alkalized titanium material; (3) The alkalized titanium material is placed horizontally in a polytetrafluoroethylene-lined reactor, such as Figure 1 As shown, 40 ml containing 0.488 g and 0.712 g of tetraethylthiuram disulfide in ethanol were poured into the polytetrafluoroethylene liner, the reactor was fastened and placed in a 200 °C forced air drying oven for reaction. After 12 h, the surface of the reactor was taken out to obtain Titanium sheet covered with coating. SEM images of the coating structure are shown in Figure 2. Figure 4 shown.
[0046] In the present invention, the iron source When the sulfur source tetraethylthiuram disulfide is dissolved in ethanol by ultrasonic treatment, it can be dissolved more evenly.
[0047] Example 2 The present embodiment provides a method for preparing an antibacterial coating on a titanium surface, which specifically includes: (1) pickling the surface of the TA2 pure titanium sheet with a mixed acid solution to obtain an acid-washed titanium material, wherein the mixed acid solution is prepared by mixing hydrofluoric acid, nitric acid and water in a volume ratio of 1:4:5; (2) placing the acid-washed TA2 pure titanium sheet in a 5 mol / L sodium hydroxide solution for alkalization for 24 h to form a sodium titanate layer to obtain an alkalized titanium material; (3) Place the alkalized titanium material vertically on Figure 2 Then 40 mL containing 0.488 g and 0.712 g of tetraethylthiuram disulfide in ethanol were poured into a polytetrafluoroethylene-lined reactor, and then the titanium mesh containing the alkalized titanium material was immersed in the solution; the reactor was tightened and placed in a 200°C forced air drying oven for reaction, and after 12 hours, the surface of the titanium mesh was taken out to obtain a titanium mesh having a Titanium sheet covered with coating. SEM images of the coating structure are shown in Figure 2. Figure 6 shown.
[0048] Example 3 The present embodiment provides a method for preparing an antibacterial coating on a titanium surface, which specifically includes: (1) pickling the surface of the TA2 pure titanium sheet with a mixed acid solution to obtain an acid-washed titanium material, wherein the mixed acid solution is prepared by mixing hydrofluoric acid, nitric acid and water in a volume ratio of 1:4:5; (2) placing the acid-washed TA2 pure titanium sheet in a 5 mol / L sodium hydroxide solution and alkalizing it for 24 hours to form a sodium titanate layer to obtain an alkalized titanium material; (3) The alkalized titanium material is vertically suspended using titanium wire or iron wire (such as Figure 3 ) In the reactor, 40 mL containing 0.488 g and 0.712 g of tetraethylthiuram disulfide ethanol solution were poured into the polytetrafluoroethylene liner, the reactor was fastened and placed in a 200°C forced air drying oven for reaction. After 12 h, the surface of the reactor was taken out to obtain Titanium sheet covered with coating. SEM images of the coating structure are shown in Figure 2. Figure 8 shown.
[0049] Comparative Example 1 In this embodiment, a preferred TA2 pure titanium sheet is used as a substrate, and a mixed acid solution is used for pickling to remove surface oxides. The mixed acid solution is prepared by mixing hydrofluoric acid, nitric acid and water in a volume ratio of 1:4:5.
[0050] Test Example 1 Use 100 µL of a 10 6 The samples prepared in Examples 1-3 and Control Example 1 were inoculated with E. coli solutions of 1000 CFU / mL respectively; after inoculation, the samples were placed in a bacterial incubator for 4 hours; then, the surface of each sample was eluted with 900 µL of saline; after elution, the eluted liquid was aspirated and transferred to a centrifuge tube, and then 10 µL of liquid was taken for coating, and 10 µL of liquid was taken from the centrifuge tube and diluted 100 times before coating. All coated culture dishes were placed in a bacterial incubator at 37°C for 18 hours. The antibacterial effect was calculated by lithographic counting.
[0051] The antibacterial efficiency of the samples was calculated using the following formula: Antibacterial efficiency
[0052] Among them, A represents the number of colonies corresponding to the sample of control example 1, and B represents the number of colonies corresponding to the sample of the experimental group.
[0053] Table 1 Antibacterial performance test of coating
[0054] From the antibacterial performance test, it can be seen that the titanium sheet with FeS2 coating has excellent antibacterial effect, and their antibacterial effects are all above 95%. Among them, the antibacterial effect of Example 3 is the best. Figure 6 As shown, this may be because Example 2 forms a more uniform and dense structure.
[0055] Test Example 2 The bacterial inoculation and culture method is as described in Test Example 1, except that after culture, 900 µL of 2.5% glutaraldehyde is added to fix the bacteria overnight. The next day, 30%, 50%, 70%, 90%, 100% and 100% anhydrous ethanol are used to dry the fixed bacteria in turn. Each interval is 10 min.
[0056] like Fig.10 As shown in Table 1, the cell membrane of E. coli on the titanium substrate is intact, indicating that the bacterial structure is not destroyed. The titanium substrate has no antibacterial effect on E. coli, which is consistent with Table 1. Figure 5 , 7 As shown in Figures 9 and 10 , the cytoplasm of bacteria flows out from the surface of the sample with the coating, and the bacteria are elongated. The coating has an antibacterial effect, which is consistent with the results in Table 1 .
[0057] Test Example 3 3,3,5,5-Tetramethylbenzidine (TMB) is usually used as a molecular probe to detect peroxidase-like properties. It can be oxidized to blue oxidized TMB in the presence of hydroxyl groups, with a characteristic absorption peak at 652 nm. After TMB, H2O2 and samples (Control Example 1, Example 1, Example 2, Example 3, 2 mM FeS2 and 2 mM FeSO4) were co-cultured at 37°C for 30 minutes, the color of the mixed solution changed significantly and turned dark blue. The purpose of testing FeSO4 is to use FeSO4 as a positive control group. The purpose of testing FeS2 is to illustrate that FeS2 powder also has the Fenton effect of catalyzing the production of hydroxyl radicals from hydrogen peroxide.
[0058] like Fig.11 As shown in the small figure, the color of the control group did not change, while the colors of the different embodiment groups all changed to blue. Fig.11 From the test results of UV-vis spectrum, it can be seen that all the example groups have a peak at 652 nm, indicating that the example groups have the ability to catalyze hydrogen peroxide to produce hydroxyl radicals. According to the test results of 2 mM FeS2, their ability to catalyze hydrogen peroxide to produce hydroxyl radicals can be attributed to FeS2.4 Finally, it should be noted that the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0059] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0060] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing an antibacterial coating on a titanium surface, characterized in that: The preparation method comprises: Pickling the surface of the titanium material to obtain the pickled titanium material; placing the acid-washed titanium material in an alkali solution for alkalization to form a sodium titanate layer, thereby obtaining an alkalized titanium material; The alkalized titanium material is vertically placed in a reaction solution containing an iron source and a sulfur source to perform a hydrothermal reaction to obtain a titanium material containing a FeS2 coating; Wherein, the iron source in the reaction solution includes any one of ferric chloride, ferrous gluconate, ferrous sulfate and ferric nitrate, and the sulfur source includes any one of tetraethylthiuram disulfide, thiourea and thioacetamide.
2. The method for preparing an antibacterial coating on a titanium surface according to claim 1, characterized in that: The pickling of the titanium material surface to obtain the pickled titanium material specifically includes: A mixed acid solution is used to pickle the surface of the titanium material to obtain a pickled titanium material; The mixed acid solution is prepared by mixing hydrofluoric acid, nitric acid and water in a volume ratio of 1:4:
5.
3. The method for preparing an antibacterial coating on a titanium surface according to claim 1, characterized in that: The step of placing the pickled titanium material in an alkaline solution for alkalization to form a sodium titanate layer to obtain an alkalized titanium material specifically includes: The acid-washed titanium material is placed in a 1-10 mol / L sodium hydroxide solution or a potassium hydroxide solution for alkalization for 20-28 hours to form a sodium titanate layer, thereby obtaining an alkalized titanium material.
4. The method for preparing an antibacterial coating on a titanium surface according to claim 1, characterized in that: The alkalized titanium material is vertically placed in a reaction solution containing an iron source and a sulfur source to perform a hydrothermal reaction to obtain a titanium material containing a FeS2 coating, which specifically includes: The alkalized titanium material is vertically placed in a reaction solution containing an iron source and a sulfur source, and a hydrothermal reaction is carried out at 140 to 200° C. The reaction time is 12 to 24 hours to obtain a titanium material containing a FeS2 coating.
5. The method for preparing an antibacterial coating on a titanium surface according to claim 1, characterized in that: In the reaction solution, the concentration of the iron source is 0.03-0.06 mol / L, and the concentration of the sulfur source is 0.04-0.08 mol / L; The solvent of the reaction solution includes ethanol.
6. The method for preparing an antibacterial coating on a titanium surface according to claim 1, characterized in that: In the reaction solution, the molar ratio of the iron source to the sulfur source is 1:4.
5.
7. The method for preparing an antibacterial coating on a titanium surface according to claim 1, characterized in that: The titanium material includes a pure titanium sheet or a titanium alloy sheet.
8. A titanium material containing FeS2 coating, characterized in that: The titanium material containing the FeS2 coating is prepared by the method for preparing an antibacterial coating on a titanium surface according to any one of claims 1 to 7.
9. Use of the method for preparing an antibacterial coating on a titanium surface as claimed in any one of claims 1 to 7 in preparing biomedical materials or medical devices.
10. Use of the titanium material containing FeS2 coating as claimed in claim 8 in the preparation of biomedical materials or medical devices.
Citation Information
Patent Citations
Molecular sieve antibacterial coating with pure titanium or titanium alloy surface and preparation method thereof
CN101791433A
Preparation method of gas purification membrane with antibacterial function
CN103537197A
Cysteine-based antibacterial nano iron sulfide mixture, and preparation method and application thereof
CN109260222A
High-efficiency antibacterial nano iron sulfide mixture as well as preparation method and application thereof
CN109364100A
Preparation method of 3D-configuration sodium titanate nanofiber coating with high bonding strength
CN112251751A